Victor Grant Collection, Album 2, Photograph 58 Emilio Valdez, Sr., and Adelina (Abreu) Valdez
Anniversary photograph, writing in album underneath photo says "1937". Third unidentified man to the far right, possibly a priest.
Designation "2.58" in listing stands for Album 2, Photograph 58.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Valdez, Emelio Sr; Valdez, Adelina Abreu; Priest; Maxwell - Beaubien family; Genealogy - Photographic collection. -- New Mexico